Modern approach to automation of internal control of quality and safety of medical care - S. Y. Morozov; M. A. Morozova; L. E. Morozova (Здоровье мегаполиса, 2022)
Introduction. Heads of medical organizations operating under the Moscow Healthcare Department are the ones who take care of internal control of quality and safety of medical care [1-7]. However, once the healthcare system in Moscow switched to the Unified Medical Information Analysis System (UMIAS), abandoning all the other automated information systems the city had previously used (such as Medialog, Megaklinika, Asclepius etc.), Moscow’s medical workers found it impossible to automatically unload certain statistical (analytical) reports. They have to use paper medical records and logs to register the results of the medical care quality control [1, 2, 6]. Many engineers and programmers working in Moscow’s medical system organizations attempted uploading the medical record data and create automated logs within the UMIAS system; however, they failed [4, 8, 9, 10]. That is why they started creating intranet web portals, integrating them with various internal Moscow healthcare systems (such as UMIAS etc.) as well as external Federal Compulsory Medical Insurance Fund systems (like the PUMP system for personalized medical care records). This allowed logging in the results of internal quality control and automatically creating statistical and analytical reports, as well as monitoring the document exchange between various offices of Moscow healthcare organizations [11-13]. To ensure the efficiency of these intranet web portals, medical workers responsible for quality control develop checklists that feature pre-approved criteria for evaluating the results of treatment for certain diseases (conditions) in accordance with medical care provision standards and clinical recommendations. Moreover, the comprehensive introduction of intranet web portals helped ensure that clinical recommendations are followed in Moscow healthcare organizations. In fact, it allowed conducting an automated medical and economic examination, similar to the ones carried out by health insurance organizations within the framework of the compulsory medical insurance system as part of state oversight.Goal. To identify the main issues in organizing internal control of quality and safety of medical care associated with the introduction of intranet web portals in Moscow healthcare system’s organizations.Materials and methods. We identified the main issues in organizing internal control of quality and safety of medical care associated with the introduction of intranet web portals in Moscow healthcare system’s organizations. Moreover, we also examined the requirements for checklist development, as well as the difficulties that arise when compiling analytical reports on following the expert criteria and standards of medical care provision and clinical recommendations.Findings. The list of the main issues associated with the introduction of an automated system for organizing internal control of quality and safety of medical care via multi-user intranet web portals includes: training heads of structural units responsible for organizing and carrying out the internal control of quality and safety of medical care; developing checklists using the pre-approved criteria, rules and requirements for providing medical care in accordance with standards and clinical recommendations; and developing an activity plan for organizing various checks (audits) and compiling analytical (statistical) reports to assess the activities of the Moscow healthcare organizations’ structural units (or employees). The checklists must feature codes of MES (medical and economic standards), ICD-10 (10th revision of the International Statistical Classification of Diseases and Related Health Problems) and medical services, as well expert criteria mentioned in acting legal documents. This is complicated by the fact that the codes of medical services in the UMIAS system differ from the codes featured in the approved medical service nomenclature, whereas expert criteria undergo frequent updates.Conclusion. To ensure the successful implementation of management responses, one needs to regularly host internal meetings with heads of structural units as well as employees responsible for organizing and carrying out internal control of quality and safety of medical care, and timely develop checklists in accordance with pre-approved standards, assessment criteria, rules and requirements of enforcement authorities while taking into account the latest clinical recommendations. To ensure proper control over following medical care provision standards in accordance with clinical recommendations and, therefore, avoid deductions and fines issued by oversight bodies, one needs to adopt a comprehensive approach to internal control of quality and safety of medical care at every level (stage), including heads of department, deputy chief doctors, deputy heads for clinical expert work etc. Keywords: intranet web portal; quality control; levels of control; control auto